Valorization of the Blends Polystyrene/LCO and Polystyrene-Butadiene/LCO over different HY Zeolites under FCC Unit Conditions - Arandes, José M. (2004)
The catalytic cracking of blends made up of polystyrene and polystyrene−butadiene with a light cycle oil (refinery stream) has been studied under the standard conditions of a FCC process. The catalysts used have been prepared based on HY zeolites of different acidity and porous structure. The results reveal the interest of the FCC process for recovering styrene and obtaining a C5−C12 pool of high aromatic content, together with a stream of olefinic gases. The presence of dissolved plastics improves conversion and yields of interesting products over that corresponding to the cracking of the solvent. The acidity of the catalyst is a limiting factor in both the catalytic activity and the formation of coke. Coke formation is largely attenuated by a steaming treatment of the zeolite, which decreases acidity and generates micropores of greater size.